Hubungan Media Sosial Terhadap Kesehatan Mental Pada Remaja Di SMA Negeri 5 Padang - Erfika Syinta Zahra; Edo Gusdiansyah; Diana Arianti (CV. ITTC INDONESIA, 2026)
Adolescence is a period of major changes in physical, sexual, psychological, and mental development that influence how teenagers respond to their environment. The increasing prevalence of emotional and mental disorders among adolescents is often associated with social media use, which can trigger anxiety and depression due to the tendency to compare themselves with others. This study aimed to determine the relationship between social media use and mental health among adolescents at SMA Negeri 5 Padang. This study used a quantitative analytical method with a cross-sectional design. The research was conducted in May 2025 and involved 89 students from grades X and XI selected through random sampling from a population of 819 students. Data were collected using a social media usage questionnaire and the Self-Reporting Questionnaire-20 (SRQ-20) and were analyzed using the Chi-square test. The results showed that 62.9% of adolescents experienced emotional mental disorders, and there was a significant relationship between social media use and mental health (p-value = 0.000). Schools are expected to provide education on mental health and the impact of social media use.